Efeito de protocolos de jateamento na resistência à flexão e transformação de fase cristalina em cerâmicas de Y-TZP - Turci, Priscilla Cristoforides Pereira [UNESP] (2014)
The aim of this study was to evaluate the effect of different sandblasting protocols on biaxial flexural strength and crystalline phase transformation in Y - TZP ceramic. 740 discs of Yttria-Partially-Stabilized Zirconia were made - Cercon ® Zirconia (DENTSPLY Ceramco, USA) and In Ceram 2000 YZ cubes (Vita Zahnfabrik, Germany) according to the standards of ISO 6872 (15 mm diameter x 2 mm thick) . The samples were sandblasted with aluminum oxide - coated silica 30 μm (Rocatec Soft - 3M ESPE ) and divided into 74 groups (n = 10 ) , according: pressure (2, 3 and 4 bar) ; nozzle angle (45°, 60°, 90°); nozzle distance (5 and 10 mm) and time (15 s and 20 s) . The biaxial flexural strength on universal testing machine (1mm/min, 1,000 kg) was performed. Data (MPa) were submitted to ANOVA and to Duncan's test (α = 0.05). Samples (n = 2) were subjected to X- ray diffraction to quantify crystalline phases. Pressure (p = 0.00) significantly affected the results, but deposition time (p = 0.49), nozzle distance (p = 0.46) and nozzle angles (p=0.13) did not affect to Cercon ceramic. Pressure (p = 0.00) affected significantly the results to Vita YZ, but deposition time (p = 0.66), nozzle distance (p = 0.70) and nozzle angles (p = 0.14) did not affect. Some monoclinical phase was achieved in Cercon groups (0 a 11%) and none for Vita YZ. For Vita YZ ceramic, 3 bar pressure had the biggest flexural strength value and 4 bar was the worst one and angle 45° associated to 2 bar were the best combination (1012.21 ± 108.36 MPa) compared to 4 bar (556.65 ± 117.41 MPa) (p < 0.001). EDS analysis demonstrated regular superficial grains. SEM images indicated grain size of 0.712 μm (Vita YZ), and 0.705 μm (Cercon). The Cercon density was 98% compared to the theoretical density of zirconia, while VITA YZ was 99%